Probable dysfunction of GABA-A receptors in patients with GNAO1-related syndromes - Pawłowicz, Małgorzata (Journal of Education, Health and Sport, 2021)
Introduction and purpose: Wide range of phenotypic spectrum of GNAO1-related syndromes includes developmental and epileptic encephalopathy (DEE) and a range of movement disorders (MDs) with or without epilepsy. Above clinical symptoms are associated with disturbances in presynaptic auto-inhibitory effect of several neurotransmitters on their receptors (M2/M4 muscarinic, α2-adrenergic, μ/δ opioid, GABA-B). Here, we analyse the phenotype-genotype correlations in patients with GNAO1-related disorders, focusing on clinical signs associated with neurotransmission disturbances. Material and methods: Clinical course of disease was evaluated in two patients of Polish origin with GNAO1-related syndromes. The diagnosis in all cases was establish on the basis of whole exome sequencing (WES) analysis on Illumina platform. All variants in GNAO1 gene occurred de novo (negative parental testing). Results: In the first patient clinically presenting symptoms of DEE the gain-of-function (GOF) (c.607G>A) variant of GNAO1 gene was identified. In this patient MDs (combination of choreathetosis and focal dystonia) co-existed with seizures. In the second patient the same combination of MDs, but without epilepsy, were caused by the pathogenic variant of unknown function (c.709G>A). In both patients significant hypersensitivity to higher doses of benzodiazepines and in the second patient also to higher doses of baclofen was noticed. In the first patient early onset of DEE (2 weeks of age) with good response of seizures to vigabatrin treatment was observed, with further development of startle response from 3 years of age with paradoxical reaction to clonazepam treatment. Conclusions: In our patients with GNAO1-related neurodevelopmental disorders we identified some drug responses or hypersensitivities which could be indicative for functional disturbances not only of GABA-B, but also GABA-A receptors. Further functional studies are needed.